2012
DOI: 10.1103/physrevd.86.104039
|View full text |Cite
|
Sign up to set email alerts
|

Stellar structure equations in extended Palatini gravity

Abstract: We consider static spherically symmetric stellar configurations in Palatini theories of gravity in which the Lagrangian is an unspecified function of the form f (R, R µν R µν ). We obtain the Tolman-Oppenheimer-Volkov equations corresponding to this class of theories and show that they recover those of f (R) theories and General Relativity in the appropriate limits. We show that the exterior vacuum solutions are of Schwarzschild-de Sitter type and comment on the possible expected modifications, as compared to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
75
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(87 citation statements)
references
References 60 publications
12
75
0
Order By: Relevance
“…The regular case somehow generalizes the solution found in [37] to cases with nonzero topological charge. We have shown that the parameter δ 1 , which is related to the constant C, is bounded below by the purely electric case.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…The regular case somehow generalizes the solution found in [37] to cases with nonzero topological charge. We have shown that the parameter δ 1 , which is related to the constant C, is bounded below by the purely electric case.…”
Section: Discussionsupporting
confidence: 68%
“…This parameter controls the traversability of the wormhole, in the sense that depending on the charge-to-mass ratio of the monopole charge an event horizon may be present or not. In [37] the wormhole is always traversable even for massive particles, without the pathologies found here regarding geodesic motion.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations